Integrative transcriptomic and proteomic analysis reveals CD9/ITGA4/PI3K‐Akt axis mediates trabecular meshwork cell apoptosis in human glaucoma. Issue 1 (3rd November 2019) - Yan, Junwei; Yang, Xuejiao; Jiao, Xuefei; Yang, Xian; Guo, Mingjin; Chen, Yunqing; Zhan, Lu; Chen, Wenshi
Abstract: Glaucoma has been the leading cause of irreversible blindness worldwide. High intraocular pressure (IOP) is a high‐risk factor of glaucoma, repression of which has been the important treatment of glaucoma in clinic. Trabecular meshwork is crucial for maintaining IOP in aqueous humour out‐flow system. It is urgent to reveal the molecular mechanism of trabecular meshwork in glaucoma. Previous studies found that some pathways were related to glaucoma, such as extracellular matrix (ECM)‐receptor interaction, phosphatidylinositol 3‐kinase (PI3K)‐protein kinase B (Akt) and apoptosis. To identify novel molecules in glaucoma, we performed high‐throughput transcriptome and proteome analysis to immortal human trabecular meshwork cells (iHTM) and glaucomatous human trabecular meshwork cells (GTM3 ), respectively. Twenty‐six up‐regulated genes/proteins and 59 down‐regulated genes/proteins were identified as the high‐risk factors based on differential analysis, including some known factors of glaucoma. Furthermore, a glaucoma‐related protein‐protein interaction (PPI) network was constructed for investigating the function roles of risk factors. Some genes were identified as potential regulator in the pathogenesis of glaucoma based on the topology analysis and module analysis to the network. Importantly, we identified and demonstrated that CD9 played key roles in glaucoma by biological experiment. CD9 is down‐regulated in glaucoma, overexpression of CD9 can active integrin α4 (ITGA4), PI3K and Akt, which lead to the decreased apoptosis and attenuate glaucoma. All these results provide a novel molecular therapy of glaucoma.